Marine Ecotourism Development Strategy Based on Creative Local Potential in Binasi Beach - Shofian Nanda Adiprayoga; Husnul Yaqin; Tirta Anugerah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
As a popular tourist attraction, the Binasi Beach ecotourism area is always busy receiving visits from domestic and foreign tourists when the holiday season arrives. However, the management of ecotourism objects is not optimal, sometimes this makes ecotourism not much visited on weekdays or on weekends. This has an impact on ecotourism activities that are not really felt by local people who depend on these ecotourism activities. The research was carried out from June to August 2023. The research used an exploratory qualitative approach. The data used uses primary data obtained through interviews with various elements and measurements of water quality and water ecology. Meanwhile, secondary data was collected from various related document sources. Data analysis was carried out using Willingness to Pay (WTP), Willingness to Accept (WTA), economic potential analysis, SWOT analysis, Reliability test and Validity test. The results of the study indicate that the development strategy can be pursued by adding supporting facilities such as providing information boards for tourists regarding directions, location of supporting facilities and the furthest water point that is safe for swimming. The addition of environmentally friendly play facilities is also highly anticipated by tourists. Creative local economic products that can be developed are Kepek Gadapang and Turtle Themed Crafts. Furthermore, the government can issue policies to provide routine guidance and access to capital for businesses run by local communities.